2017
DOI: 10.1111/coa.12836
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing outcomes for patients with oropharyngeal squamous cell carcinoma treated with primary (chemo)radiation therapy receiving either prophylactic gastrostomy or reactive nasogastric tube: A prospective cohort study

Abstract: There is no statistical difference for swallowing outcomes in either group. However, patients' in the rNGT group reported a clinically meaningful difference at 1 year, with a trend for them to do better across all measures. Neither group returned to their baseline swallowing function. Further research with a larger sample size is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…A prior randomised study was converted to a prospective study after poor accrual [17]; in this study, an analysis of 32 PEG and 73 NG patients grade 3 dysphagia was found to significantly higher 6 months post treatment for PEG patients. A recent prospective cohort study [22] of 53 oropharyngeal cancer patients with normal pretreatment diet found higher MDADI scores at 12 months post treatment for patients managed with a reactive NG tube vs. a prophylactic gastrostomy (mean total MDADI 72.3 vs. 61.2) although differences were not statistically significant. In a retrospective analysis of 120 patients treated with chemoradiotherapy for head and neck cancer [21], gastrostomy dependence was higher at 12 months following a prophylactic gastrostomy (21% vs. 0%].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A prior randomised study was converted to a prospective study after poor accrual [17]; in this study, an analysis of 32 PEG and 73 NG patients grade 3 dysphagia was found to significantly higher 6 months post treatment for PEG patients. A recent prospective cohort study [22] of 53 oropharyngeal cancer patients with normal pretreatment diet found higher MDADI scores at 12 months post treatment for patients managed with a reactive NG tube vs. a prophylactic gastrostomy (mean total MDADI 72.3 vs. 61.2) although differences were not statistically significant. In a retrospective analysis of 120 patients treated with chemoradiotherapy for head and neck cancer [21], gastrostomy dependence was higher at 12 months following a prophylactic gastrostomy (21% vs. 0%].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies are limited by potential confounding factors affecting why patients had received a prophylactic gastrostomy rather than a reactive approach to feeding [17,[21][22][23][24]38]. Clinicians may be more likely to recommend a prophylactic gastrostomy tube to patients they consider at higher risk of requiring enteral feeding support i.e., in patients with more advanced/bulky disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing question in our field as to whether prophylactic feeding tube placement may contribute to long‐term dysphagia. Past studies have had mixed results, with some showing better long‐term quality of life and shorter tube dependence without prophylactic gastrostomy tube placement and others refuting this . Unfortunately, we are unable to determine definitively from our data which gastrostomy tubes were placed prophylactically and which were placed reactively, therefore, we were unable to analyze the possible contribution of this risk factor.…”
Section: Discussionmentioning
confidence: 75%
“…However, the present literature is ambiguous on the relationship between prophylactic TF and long-term OD. 18,[62][63][64][65][66] Therefore, supplemental TF to maximize the chance to reach the nutritional target remains to be a regime that deserves validation.…”
Section: Discussionmentioning
confidence: 99%